1997
DOI: 10.1016/s0092-8674(00)80257-3
|View full text |Cite
|
Sign up to set email alerts
|

Osf2/Cbfa1: A Transcriptional Activator of Osteoblast Differentiation

Abstract: The osteoblast is the bone-forming cell. The molecular basis of osteoblast-specific gene expression and differentiation is unknown. We previously identified an osteoblast-specific cis-acting element, termed OSE2, in the Osteocalcin promoter. We have now cloned the cDNA encoding Osf2/Cbfa1, the protein that binds to OSE2. Osf2/Cbfa1 expression is initiated in the mesenchymal condensations of the developing skeleton, is strictly restricted to cells of the osteoblast lineage thereafter, and is regulated by BMP7 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

127
3,209
8
57

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 3,916 publications
(3,401 citation statements)
references
References 30 publications
127
3,209
8
57
Order By: Relevance
“…We considered that the defective calci®cation in the homozygous (7/7) mice was due to the lack of opn gene expression. Previous reports indicated that PEBP2aA regulated not only the opn gene but also BSP, osteocalcin and type I collagen gene in vitro (Ducy et al, 1997). In the present study, direct regulation of opn gene expression controlled by PEBP2aA and ETS1 was shown.…”
Section: Discussionsupporting
confidence: 69%
“…We considered that the defective calci®cation in the homozygous (7/7) mice was due to the lack of opn gene expression. Previous reports indicated that PEBP2aA regulated not only the opn gene but also BSP, osteocalcin and type I collagen gene in vitro (Ducy et al, 1997). In the present study, direct regulation of opn gene expression controlled by PEBP2aA and ETS1 was shown.…”
Section: Discussionsupporting
confidence: 69%
“…Conversely, with aging, commitment of murine MSCs to the adipogenic lineage is enhanced at the expense of osteogenesis [40], a phenotype which correlates with increased levels of PPARγ-2 [40]. While PPARγ-2 is essential to drive adipogenesis from MSCs [38,43], Runx2 (Cbfa1) seems to be the key player for osteoblast differentiation [41][42][43]. Our results show that Pax3 overexpression blocks adipogenesis, osteogenesis, and chondrogenesis potentially by inhibiting PPARγ-2 and Cbfa-1.…”
Section: Discussionmentioning
confidence: 76%
“…Luciferase assay was performed by using the Dual Luciferase Reporter Assay kit, according to the manufacturer's protocol (Promega, Madison, WI, USA). Briefly, C2C12 cells were cultured in serum-free medium in 96-well assay plates and transfected with 200 ng/well reporter plasmid, p6OSE2-Luc or p6mutOSE2-Luc, (34) plus 20 ng/well control plasmid, Renilla luciferase plasmid (pRL-TK). After 24 hours of incubation, cells were replenished with fresh medium containing vehicle, BMP2 alone, or BMP2 plus 5 mM SP600125 (Calbiochem).…”
Section: Transient Transfection and Luciferase Assaymentioning
confidence: 99%